Analisis Pembelajaran Karya Seni Motif, Tari, dan Ukiran Pada Mata Pelajaran Seni Budaya Melayu Riau Dalam Menumbuhkan kreativitas Siswa kelas V - Purnomo, Dian; Yasnel; Syofiyanti, Dessy (IJPSE Indonesian Journal of Primary Science Education, 2024)
The lack of creativity faced by students, including a lack of self-confidence, is the main factor that also causes difficulties in thinking. This has to do with students who are not confident and lack confidence to explore creativity, feeling unprepared. The lack of effective models or support also contributes to difficulties in the creative experience. In the Learning of Motifs, Dances, and Carvings in the Riau Malay Cultural Arts Subject in Fostering Student Creativity. Qualitative research method with a descriptive approach. The data sources in this study were schools, waka kurukilum, 2 cultural arts teachers and 5 MI grade viii (eight) students. Data collection by means of documentation, interviews, and observations. The results of the research discussed gave the result that learning Motif Artworks, Dances, and Carvings in the Riau Malay Cultural Arts Subject can foster creativity in students. The conclusion of the study states that it is important to learn Motif Artworks, Dance, and Carving in Malay Cultural Arts subjects to be improved, not only students' creativity but also to think critically.